Intrauterine Intussusception Presenting as Fetal Ascites and Meconium Peritonitis - Binti Kamilen, Khalilah Alhuda; Othman, Mohd Yusran (International Journal of Human and Health Sciences (IJHHS), 2021)
Intussusception is a well-known cause of intestinal obstruction in children. Its occurrence in fetus as an intrauterine incidence is extremely rare and poses a diagnostic difficulty. Intrauterine intussusception may result in intestinal atresia once the gangrenous segment resorbed. However, a very late occurrence of intussusception just prior to delivery may present as meconium peritonitis. We are reporting a case of premature baby who was born at 35 weeks gestation via emergency caesarean for breech in labour. Routine scan 4 days prior to the delivery showed evidence of fetal ascites. She was born with good Apgar Score and weighed 2.5kg. Subsequently she developed respiratory distress syndrome requiring mechanical ventilation. She passed minimal meconium once after birth then developed progressive abdominal distension and vomiting. Abdominal radiograph on day 4 of life revealed gross pneumoperitoneum and bedside percutaneous drain was inserted to ease the ventilation. Upon exploratory laparotomy, a single ileal perforation was seen 20cm from ileocecal junction with an intussusceptum was seen in the distal bowel. Gross meconium contamination and bowel edema did not favour the option of primary anastomosis, thus stoma was created. Reversal of stoma was performed a month later and she recovered well. Fetus with a complicated intrauterine intussusception may present with fetal ascites and their postnatal clinical and radiological findings need to be carefully assessed for evidence of meconium peritonitis; in which a timely surgical intervention is required to prevent the sequelae of prolonged intraabdominal sepsis in this premature baby. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S18